2015
DOI: 10.3390/vetsci2030150
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Drug Resistance in Veterinary Oncology— A Review with an Emphasis on Canine Lymphoma

Abstract: Drug resistance (DR) is the major limiting factor in the successful treatment of systemic neoplasia with cytotoxic chemotherapy. DR can be either intrinsic or acquired, and although the development and clinical implications are different, the underlying mechanisms are likely to be similar. Most causes for DR are pharmacodynamic in nature, result from adaptations within the tumor cell and include reduced drug uptake, increased drug efflux, changes in drug metabolism or drug target, increased capacity to repair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 161 publications
(205 reference statements)
1
34
0
2
Order By: Relevance
“…While chemotherapy effects only last as long as the drugs remain in the body, immunotherapy can provide long-term protection against cancer due to the immune memory, overcoming the “honeymoon effect” provided in the short term by cytotoxic drugs, more over if negative prognostic factors are present. Chemotherapy fails when drug-resistant clones emerge, preventing tumor cell eradication [23]. It may be possible that dogs with negative prognostic factors, such as advanced disease stage and high LDH levels, are more susceptible of developing chemo-resistance [2, 24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…While chemotherapy effects only last as long as the drugs remain in the body, immunotherapy can provide long-term protection against cancer due to the immune memory, overcoming the “honeymoon effect” provided in the short term by cytotoxic drugs, more over if negative prognostic factors are present. Chemotherapy fails when drug-resistant clones emerge, preventing tumor cell eradication [23]. It may be possible that dogs with negative prognostic factors, such as advanced disease stage and high LDH levels, are more susceptible of developing chemo-resistance [2, 24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its expression in somatic tissues, P‐GP can be expressed in a variety of tumor tissues in dogs and cats, and is considered one of the many mechanisms associated with chemotherapy resistance . High tumor cell P‐GP expression has been correlated with an inferior oncologic outcome in several studies of canine lymphoma, but other studies have not identified significant correlations …”
Section: P‐glycoprotein Mutation and Expression To Predict Chemotheramentioning
confidence: 99%
“…To quote Seelig, “In both species diffuse large B-cell lymphoma (DLBCL) is the most common subtype (of lymphoma), but this is where the similarities end.” Their article, like all the others in this collection, is heavily cited to provide the reader abundant background material and context. Back-to-back articles by Tomiyasu and Tsujimoto [ 8 ] and by Zandvliet and Teske [ 9 ] offer a glimpse into mechanisms of drug resistance with emphasis on lymphoma.…”
Section: Editorialmentioning
confidence: 99%